Pemenuhan Nafkah Keluarga Buruh Nelayan Pasca Pandemi Covid-19 ditinjau dari Hifz Al-Maal Dan Hifz Al-Nasl Menurut Jasser Auda : Studi Kasus di Desa Kedungrejo Kecamatan Muncar Kabupaten Banyuwangi - Cholidah, Faizatul (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2023)
This research discusses the concept of Family Livelihood Fulfillment for Fishermen Labor Post Covid-19 Pandemic (Case Study in Kedungrejo Village, Muncar Sub-district, Banyuwangi Regency) in terms of Hifz Al-Maal and Hifz Al-Nasl according to the perspective of Jasser Auda. This researchaddresses two crucial questions. First, what efforts have been made to fulfill the livelihood of fishermen labor families post the Covid-19 pandemic in Kedungrejo Village, Muncar Sub-district, Banyuwangi Regency? Second, how is the fulfillment of livelihood for fishermen labor families viewed through the Sharia objectives of Hifz Al-Maal and Hifz Al-Nasl according to Jasser Auda?The endeavor to answer these questions is an initial step in the academic world to examine the livelihood fulfillment later evaluated from Hifz Al-Maal (preservation of wealth) and Hifz Al-Nasl (preservation of progeny) according to Jasser Auda (Contemporary Fiqh Scholar). This journal reveals two main findings. First, the families of fishermen laborers have been fulfilling their daily livelihood needs by engaging in various efforts (work). Second, the efforts made by these families have successfully met the objectives of Hifz Al-Maal and Hifz Al-Nasl, particularly for the well-being of family members. The fulfillment of daily needs encompasses not only financial aspects but also basic necessities (clothing, food, shelter), health, and education.